Perancangan dan Implementasi Lampu Otomatis Berbasis IoT Menggunakan Aplikasi Blynk: Penelitian - Daniswara; Triana Puspa Handayani; Muhammad Fakhri Fauzar; Dicky Apdilah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The development of Internet of Things (IoT) technology allows remote control of electrical devices via the internet network. One application is in lighting systems to improve energy efficiency and user comfort. This study aims to design and implement an IoT-based automatic lighting system using the Blynk application as a control and monitoring medium. The method used is an experimental method with an engineering approach, including the system design stage, hardware assembly, programming, integration with the Blynk application, and system testing. The main devices used are NodeMCU/ESP32, relay modules, and AC lamps. The test results show that the system is able to control the lights in real-time via a smartphone with a good response as long as the internet connection is stable. This system has proven effective in providing convenience, flexibility, and has the potential to save electricity usage, making it suitable for application as a simple smart home solution and IoT learning medium.